PENGARUH PERSEPSI HARGA, KUALITAS PRODUK, LAYANAN PURNA JUAL DAN REPUTASI MEREK TERHADAP KEPUASAN PELANGGAN DAN DAMPAKNYA PADA PEMBERIAN REKOMENDASI KEPADA CALON PELANGGAN YANG LAIN (Students' Journal of Accounting and Banking, 2013)
The study is purposed for examining effect of perceived price, product quality, after-sales service, and brand reputation on customer satisfaction and then impacts on their recommendation to other potential customers, in the perspective of heavy equipment marketing business. The observation is focused on the heavy equipment user companies as respondents, that using the SAKAI single drum vibrating roller from 10.5 tons up to 13 tons operating weight, the series of SV512-H and SV515-H including each variant of types. The companies should be in the DKI Jakarta territorial based, and they bought the SAKAI product and being customers of the PT Equipindo Perkasa as the distributor. Judgment sampling is used as a sampling method, and the data are collected from the respondents with questionnaire by mail survey. The Structural Equation Model (SEM) is used for statistical data analysis. The study result shows that brand reputation has significant effect on customer satisfaction and then customer satisfaction significantly affects on their recommendation to other potential customers. Nevertheless customer satisfaction is not effected significantly by perceived price, product quality and after-sales service. Keywords: Perceived Price, Product Quality, After-Sales Service, Brand Reputation, Customer Satisfaction, Recommendation.